Sexual Function and Quality of Life in Cervical Cancer Survivors After Therapy: A Post COVID-19 Updated Scoping Review - Santi Susanti; Yanti Hermayanti; Ida Maryati (Greenation Publisher & Yayasan Global Research National, 2026)
Cervical cancer survivors frequently experience long-term physical and psychosocial sequelae after therapy, with sexual dysfunction and impaired quality of life (QoL) being among the most significant concerns. The COVID-19 pandemic has further disrupted cancer care, potentially altering survivorship outcomes. Purpose: This scoping review aimed to map and synthesize recent evidence (2022–2025) on sexual function and QoL among cervical cancer survivors after therapy in the post-pandemic context. Methods: A scoping review was conducted following the PRISMA-ScR framework. Articles were identified through PubMed, Scopus, and EBSCOhost: Medline Ultimate using keywords related to sexual function, QoL, cervical cancer, and post-therapy. Eligible studies were observational, published in English, and focused on survivors’ sexual function and QoL after treatment. Twenty studies met the inclusion criteria and were analyzed thematically using a descriptive exploratory approach. Results: A total of 20 articles were analyzed in this review. Majority of studies reported a high prevalence of sexual dysfunction post-therapy, including decreased desire, lubrication problems, dyspareunia, and reduced satisfaction. Although some intervention studies demonstrated improvements, sexual function generally remained impaired. QoL outcomes were more heterogeneous; several studies indicated poor QoL due to treatment-related symptoms (pain, fatigue, urinary and gastrointestinal dysfunction), while others found that more than half of survivors maintained good QoL. Conclusion: Sexual dysfunction remains a pervasive issue among cervical cancer survivors, while QoL outcomes vary depending on treatment modalities, psychosocial support, and coping strategies. A multidisciplinary survivorship approach including medical, psychological, and sexual health support is essential to improve post-therapy well-being in the post-COVID-19 era.